Battery and electric device

By setting the negative electrode active material layer of silicon-based material on the negative electrode sheet of the battery, and controlling the cohesion, separator exceeding the size and silicon element content, the problem of volume expansion and ductility increase caused by silicon-based material is solved, and the high energy density, good cycle performance and safety performance of the battery are achieved.

CN119601751APending Publication Date: 2025-03-11CALB (JIANGMEN) CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411807308.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Silicon-based anode material causes volume expansion and increased ductility in the battery, increasing the risk of shorting between the negative and positive electrode sheets, affecting the safety and electrochemical performance of the battery.

Method used

By providing a negative electrode active material layer on the current collector surface of the negative electrode sheet, including a silicon-based material, and comprehensively controlling the cohesion of the negative electrode sheet, the separator exceeds the size of the negative electrode sheet and the mass percentage of silicon elements, ensuring that A1/2*C/B is within the range of 0.03-3.

Benefits of technology

It achieves the improvement of its energy density and circulation performance on the basis of taking into account the safety performance of the battery, and avoids the risk of short-connection of the negative and positive electrode plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179600000000141
    Figure BDA0005179600000000141
  • Figure BDA0005179600000000151
    Figure BDA0005179600000000151
  • Figure BDA0005179600000000161
    Figure BDA0005179600000000161
Patent Text Reader

Abstract

The invention discloses a battery and a power utilization device, the battery comprises a negative plate, a positive plate and a diaphragm, the negative plate comprises a current collector and a negative active material layer arranged on the surface of the current collector, and the negative active material layer comprises a silicon-based material; the cohesive force of the negative plate is A, and the unit is N / m; the diaphragm which is parallel to the tab leading-out direction and close to the tab side exceeds the negative plate, the size of the diaphragm exceeding the negative plate is B, and the unit is mm; the mass percent of the silicon element in the negative electrode active material layer is C; a, B and C satisfy the following relation: 0.03 < = A1 / 2 * C / B < = 3. According to the invention, the value of A1 / 2 * C / B is comprehensively controlled in a range of 0.03-3, so that the battery with high safety performance can be obtained, and meanwhile, the battery can be ensured to have relatively good energy density and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a battery and an electrical device. Background Art

[0002] In order to obtain a high theoretical gram capacity in the battery, it is usually necessary to use silicon-containing negative electrode active materials in the negative electrode sheet; however, the application of silicon-based negative electrode materials also faces some challenges and limitations. For example, the volume expansion of silicon negative electrode materials is as high as 300%. When the negative electrode sheet contains silicon material, the negative electrode sheet has greater ductility. The extension of the negative electrode sheet increases the risk of short circuit between the negative electrode sheet and the positive electrode, thereby affecting the safety of the battery cell. Summary of the invention

[0003] Therefore, the purpose of the present invention is to provide a battery and an electrical device that ensures electrochemical properties such as energy density and cycle performance while taking into account battery safety performance.

[0004] To achieve the above object, the present invention provides a battery, including a negative electrode sheet, a positive electrode sheet and a separator, the negative electrode sheet includes a current collector and a negative electrode active material layer arranged on the surface of the current collector, the negative electrode active material layer includes a silicon-based material, the cohesive force of the negative electrode sheet is A, the unit is N / m; parallel to the direction of the tab lead-out, the separator is arranged beyond the negative electrode sheet near the tab side, the dimension of the separator beyond the negative electrode sheet is B, the unit is mm; the mass percentage of silicon element in the negative electrode active material layer is C; the A, B and C satisfy the following relationship: 0.03≤A 1 / 2 *C / B≤3.

[0005] The present invention provides an electrical device comprising the battery.

[0006] The beneficial effects of the present invention are:

[0007] A battery disclosed in the present invention comprises a negative electrode sheet, a positive electrode sheet and a separator, wherein the negative electrode sheet comprises a current collector and a negative electrode active material layer arranged on the surface of the current collector, wherein the negative electrode active material layer comprises a silicon-based material; wherein the cohesive force of the negative electrode sheet is A, in N / m; parallel to the direction of the lead-out of the tab, the separator is arranged to extend beyond the negative electrode sheet near the tab side, and the dimension of the separator extending beyond the negative electrode sheet is B, in mm; the mass percentage of silicon in the negative electrode active material layer is C; the present invention achieves a battery having a silicon-based material layer, wherein the silicon-based material layer has ... 1 / 2 *Within the range of C / B≤3, we can obtain a battery with high safety performance while ensuring that the battery has good energy density and cycle performance. DETAILED DESCRIPTION

[0008] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0009] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0010] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 50%-90% and 60%-80% is listed for a particular parameter, it is understood that the range of 50% to 80% and 60% to 90% is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In this application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0.5-4" means that all real numbers between "1-4" have been listed in this article, for example: 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, etc. "0.5-4" is just an abbreviation of these numerical combinations.

[0011] The present invention provides a battery, comprising a negative electrode sheet, a positive electrode sheet and a separator, wherein the negative electrode sheet comprises a current collector and a negative electrode active material layer arranged on the surface of the current collector, wherein the negative electrode active material layer comprises a silicon-based material, wherein the cohesive force of the negative electrode sheet is A, and the unit is N / m; parallel to the direction in which the tab is led out, the separator is arranged to extend beyond the negative electrode sheet near the tab side, and the dimension of the separator extending beyond the negative electrode sheet is B, and the unit is mm; the mass percentage of silicon element in the negative electrode active material layer is C; wherein A, B, and C satisfy the following relationship: 0.03≤A 1 / 2 *C / B≤3. In the present invention, A 1 / 2 *The value of C / B can be any value between 0.03-3, for example: 0.03, 0.05, 0.1, 0.3, 0.5, 1, 1.5, 2, 2.5, 3, etc.

[0012] In the present invention, C is the mass percentage of silicon in the negative electrode active material layer. By adding silicon material to the negative electrode active material layer, the overall energy density of the battery can be improved. A is the cohesive force of the negative electrode sheet, and the cohesive force refers to the bonding force between the negative electrode active particles in the negative electrode active coating. B is the size of the diaphragm exceeding the negative electrode sheet in the direction close to the tab; the diaphragm is arranged between the positive and negative electrode sheets to avoid short circuits between the positive and negative electrode sheets. In order to ensure that there is no short circuit between the positive and negative electrode sheets, the diaphragm is generally arranged beyond the negative electrode sheet; the tab bears the overcurrent, and the current density near the tab is relatively large. The negative electrode active material layer near the tab first begins to undergo an electrochemical reaction of lithium ion embedding, and the negative electrode sheet is more extended, which is easy to cause a short circuit with the positive electrode sheet, resulting in an internal short circuit.

[0013] The present application achieves the purpose of ensuring the electrochemical properties such as energy density and cycle performance while taking into account the safety performance of the battery by comprehensively controlling the mass proportion C of the silicon element, the cohesive force A of the negative electrode sheet, and the relationship between the size B of the diaphragm super-negative electrode sheet in the direction close to the pole ear. Specifically, by adding silicon material to the negative electrode sheet, the overall energy density of the battery is improved; but it is precisely based on the addition of silicon material that the volume expansion of the negative electrode sheet increases, which in turn causes the extension of the negative electrode sheet to increase; the cohesive force reflects the bonding force between the active particles of the negative electrode. If the cohesive force is small, the bonding strength between the particles is weak, and the expansion of the thickness of the electrode sheet is large, which easily leads to the loss of electrical contact between the active material and the current collector, resulting in rapid capacity decay and poor cycle performance; if the cohesive force is too large, the extension of the negative electrode sheet increases, which easily causes the negative electrode sheet and the positive electrode sheet to short-circuit. It is necessary to match the size of the larger diaphragm super-negative electrode sheet to avoid the occurrence of short circuit in the battery, but correspondingly, the space utilization rate of the battery will be reduced, the battery energy density will be low, the space will be wasted, and the internal resistance of the battery may be increased, affecting the transmission speed of lithium ions, increasing capacity decay, and thus reducing the cycle performance of the battery. The present invention performs power processing on the cohesion A to smooth its data changes, thereby achieving more reasonable data analysis and application; in summary, in the present invention, if A 1 / 2 *C / B is too large, the silicon content increases, the cohesive force is large, the pole piece extension increases, the diaphragm is too small, and the positive and negative poles are short-circuited. If A 1 / 2 *C / B is too small, the silicon content is small, the energy density is low, the separator is smaller than the negative electrode sheet, and the battery energy density is low; the cohesion is too small, the bonding strength between particles is weak, and the expansion of the electrode sheet thickness is large, which easily leads to the loss of electrical contact between the active material and the current collector, resulting in rapid capacity decay and poor cycle performance; that is, the present invention comprehensively controls A 1 / 2 * When C / B is in the range of 0.03-3, a battery with high safety performance can be obtained while ensuring that the battery has high electrochemical properties such as high energy density and cycle performance.

[0014] Furthermore, by1 / 2 *The value of C / B is controlled within a more preferred range of 0.045-1.4, and the comprehensive performance of safety performance, energy density and cycle performance of the present invention is better.

[0015] In one preferred embodiment, the value range of the cohesive force A of the negative electrode sheet is 0.3-220 N / m, preferably 5-150 N / m; the cohesive force A of the negative electrode sheet represents the bonding strength between particles in the negative electrode active material layer. The value of A should not be too high or too low; if the value of A is too low, the bonding strength between particles is weak, and the expansion of the electrode sheet thickness is large, resulting in the loss of electrical contact between the active material and the current collector, causing rapid capacity decay and poor cycle performance; while if the value of A is too high, although the expansion of the negative electrode sheet in the thickness direction is suppressed, the extension in the horizontal direction will increase, and the extension of the negative electrode sheet in the horizontal direction is controlled, reducing the risk of short circuit with the positive terminal. For example: control A to 0.3N / m, 0.5N / m, 1N / m, 3N / m, 5N / m, 7N / m, 10N / m, 30N / m, 50N / m, 80N / m, 100N / m, 120N / m, 150N / m, 180N / m, 200N / m, 220N / m, etc.

[0016] The present invention does not limit the method for adjusting the value of the cohesive force A of the negative electrode sheet. For example, it can be adjusted by adjusting the type and ratio of the binder in the negative electrode sheet preparation process, or it can be adjusted by parameters such as temperature and pressure. In this application, it is mainly adjusted by the type and ratio of the binder.

[0017] In one preferred embodiment, the value range of B is 1-4 mm. The value range of B should not be too large or too small; if B is too large, the space utilization rate of the battery will be reduced, the space will be wasted, the battery energy density will be reduced, and the internal resistance may be increased, affecting the cycle performance; if B is too small, the extension requirements of the negative electrode sheet cannot be met, affecting safety; in the present invention, the value of B is controlled to 1-4 mm, preferably 1.5-3 mm, which can effectively take into account safety performance, energy density and cycle performance; for example, the value of B can be controlled to be 1, 1.5, 2, 2.5, 3, 3.5, 4, etc.

[0018] In one preferred embodiment, C is controlled within a suitable range, which can improve the battery energy density while avoiding excessive extension of the negative electrode sheet to ensure safety performance. The value range of C should not be too large or too small; if the C value is too small, the energy density is too low; if the C value is too high, the silicon element will have a large volume expansion during the charging and discharging process, and the corresponding negative electrode sheet will also extend too much in the horizontal direction, which is easy to exceed the diaphragm and short-circuit the positive electrode sheet; the present invention can improve the battery energy density and avoid excessive extension of the negative electrode sheet to ensure safety performance by controlling the percentage content C of the silicon element in the negative electrode active material layer to 1.5%-30%, preferably 4%-20%; for example: the mass percentage C of the silicon element in the negative electrode active material layer is controlled to be 1.5%, 2%, 3%, 5%, 10%, 12%, 15%, 20%, 25%, 30%, etc.

[0019] The present invention further optimizes the surface density of the negative electrode active material layer. If the surface density is too small, the negative electrode capacity is low, and if the surface density is too large, the electrode sheet will be extended and the risk of short circuit with the positive electrode sheet will increase. Therefore, the surface density in the present invention is 60-300g / m 2 ; For example: control the surface density to 60g / m 2 , 80g / m 2 , 100g / m 2 , 150g / m 2 , 200g / m 2 , 250g / m 2 , 300g / m 2 wait.

[0020] The present invention does not limit the method for adjusting the surface density of the negative electrode active material layer. For example, the surface density of the negative electrode active material layer in the present invention can be adjusted by parameters such as coating thickness, reduction rate, temperature, etc. in the negative electrode sheet process.

[0021] In the present invention, as an optional manner, the silicon-based material includes silicon-carbon material and / or silicon-oxygen material; specifically, the silicon-based material can be one or more of silicon-carbon composite negative electrode material, silicon monoxide negative electrode material, modified silicon monoxide negative electrode material, and nano-silicon material.

[0022] When the silicon-based material includes a silicon-carbon material, the silicon-carbon material is a silicon-carbon composite negative electrode material, which includes a porous carbon matrix and silicon particles deposited on the porous carbon matrix. The porous carbon matrix acts as a buffer space to reduce the volume expansion of the negative electrode during the charge and discharge process. Therefore, when the silicon-based material includes a silicon-carbon material, the porous carbon can alleviate the expansion of the negative electrode, further reducing the volume expansion of the negative electrode during the charge and discharge process. 1 / 2 *C / B is controlled within 0.045-1, further improving energy density while taking into account cycle performance.

[0023] Furthermore, the negative electrode active material layer also includes one or more of artificial graphite, natural graphite, and hard carbon.

[0024] The following discloses an embodiment of an electrochemical device and an electrical device of the present invention as appropriate. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.

[0025] [Battery]

[0026] The battery in the present invention is a secondary battery, also known as a rechargeable battery or storage battery, which refers to a battery that can be continuously used by activating the active material by charging after the battery is discharged.

[0027] Normally, a secondary battery includes an electrode assembly, an electrolyte and an outer packaging shell. The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The electrode assembly and the electrolyte are assembled in the outer packaging shell. During the battery charging and discharging process, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time to allow active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.

[0028] As an example, the preparation process of a secondary battery is as follows: stack the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wind or stack the sheets to obtain an electrode assembly; place the electrode assembly in an outer packaging shell, inject electrolyte after drying, and obtain a secondary battery through vacuum packaging, standing, formation, shaping and other processes.

[0029] [Positive electrode]

[0030] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector. The positive electrode film layer includes a positive electrode active material, which can be any positive electrode active material disclosed in the prior art or a positive electrode active material optimized on the prior art basis.

[0031] The present invention has no particular restrictions on the type of positive electrode active material of the positive electrode sheet. As an example, the positive electrode active material in the present invention includes lithium-containing transition metal oxides (e.g., LiCoO2), phosphides (e.g., LiFePO4) or lithium-embedded compounds (e.g., lithium cobalt oxide, lithium nickel oxide and other positive electrode materials for binary lithium batteries, or lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and other positive electrode materials for ternary lithium batteries).

[0032] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (for example, N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling, cutting and other processes, the positive electrode sheet can be obtained.

[0033] In the present invention, the binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. The present invention does not particularly limit the type of binder for the positive electrode sheet, and the binder in the present invention can be a conventional choice in the battery field. Specifically, the binder can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.

[0034] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.

[0035] [Negative electrode]

[0036] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer includes a silicon-based material. The present invention has no specific restrictions on the type of silicon-based material, and the silicon-based material may be a silicon-carbon material and / or a silicon-oxygen material. As an example, the silicon-based material may be one or more of a silicon-carbon composite negative electrode material, a silicon oxide negative electrode material, a modified silicon oxide negative electrode material, and a nano-silicon material. The negative electrode active material in the negative electrode active material layer may also optionally include one or more of artificial graphite, natural graphite, and hard carbon.

[0037] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling, cutting and other processes, the negative electrode sheet can be obtained.

[0038] The present invention has no specific limitation on the type of negative electrode conductive agent. In some embodiments, as an example, the negative electrode conductive agent can be one or more conventional negative electrode conductive agents such as acetylene black and carbon nanotubes;

[0039] The present invention has no specific limitation on the type of negative electrode binder. In some embodiments, as an example, the binder can be one or more conventional negative electrode binders such as styrene-butadiene rubber latex (SBR), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), etc.; in the present invention, the binder is preferably PAA, SBR and CMC, and the mass ratio of PAA, SBR and CMC can be (34.38-74.29): (20-59.38): (5-7.14).

[0040] The present invention has no specific limitation on the type of the negative electrode current collector. In some embodiments, as an example, the negative electrode current collector may be one of conventional negative electrode current collectors such as copper foil.

[0041] [Electrolyte]

[0042] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present invention has no specific restrictions on the type of electrolyte, which can be selected according to needs. As an example, the electrolyte of the present invention can be various electrolytes suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte can generally include a lithium salt, and additives can also be added to the electrolyte.

[0043] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte in the electrolyte may be 0.5 to 5 mol / L.

[0044] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0045] In some embodiments, as examples, the additive may be conventional electrolyte additives such as fluoroethylene carbonate (FEC), chloroethylene carbonate (CEC), and vinylene carbonate (VC).

[0046] [Diaphragm]

[0047] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0048] In some embodiments, as an example, the diaphragm can be one of PP, PE, and PP / PF; the diaphragm can also be a structure in which a coating is provided on the surface of a base film, wherein the base film coating can be one of PP, PE, and PP / PF, and the coating is an inorganic coating and / or an organic coating, the inorganic coating can be selected from alumina ceramic layer, beryl, etc., and the organic coating can be selected from PVDF, etc.

[0049] Examples and Comparative Examples

[0050] A battery includes a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and an outer packaging shell. The preparation process of the battery is as follows:

[0051] 1. Preparation of positive electrode

[0052] The specific preparation process of the positive electrode sheet is as follows: obtain the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), the positive electrode active material NCM811, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 96:2:2, and the solvent NMP is added, and the system is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is coated on both surfaces of the aluminum foil, and after drying at room temperature, it is transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0053] 2. Preparation of negative electrode sheet

[0054] The specific preparation process of the negative electrode sheet is as follows: the negative electrode active material graphite and the silicon-based material are mixed in a mass ratio as shown in Table 1 to obtain a mixture, the mixture is mixed with a conductive agent acetylene black, a conductive agent SWCNT, and a binder to obtain a total mixture, wherein the addition amount of the conductive agent acetylene black is 0.95% of the total mixture, the addition amount of the conductive agent SWCNT is 0.05% of the total mixture, the addition amount of the binder and its composition are shown in Table 1, deionized water is added and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is coated on both surfaces of the copper foil, and after drying at room temperature, it is transferred to an oven for further drying, and after drying, it is cold pressed and cut to obtain a compacted density of 1.42 g / cm 3 Negative electrode.

[0055] 3. Obtaining the diaphragm

[0056] The diaphragm in this embodiment is a diaphragm with a coating, the base film in the diaphragm is selected to be polyethylene (PE), and the coating is an alumina ceramic layer. Based on the requirements of the diaphragm size B exceeding the negative electrode sheet shown in Table 2, a PE diaphragm of corresponding size is cut.

[0057] 4. Preparation of electrolyte

[0058] The electrolyte preparation process is as follows: in a glove box filled with argon, fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and propylene carbonate (PC) are mixed in a mass ratio of 15:20:60:5 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent, followed by adding 0.5% 1,3-propane sultone, 0.5% tris(trimethylsilyl) phosphate, and 1% vinyl sulfate to the electrolyte, and stirring until completely dissolved to form an electrolyte with a lithium salt concentration of 1.3M.

[0059] 5. Assembly of secondary batteries

[0060] The specific process is: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain an electrode assembly; place the electrode assembly in an outer packaging shell, inject electrolyte after drying, and undergo conventional vacuum packaging, standing, formation, shaping and other processes to obtain a lithium-ion secondary battery.

[0061] In the above embodiments and comparative examples, the test methods for the surface density ρ of the negative electrode sheet, the cohesive force A of the negative electrode sheet, the dimension B of the separator beyond the negative electrode sheet, and the mass percentage C of silicon in the negative electrode active material layer are as follows:

[0062] 1. Test of surface density ρ:

[0063] Use a sampler to sample the negative electrode sheet and weigh the weight of the sample m1. Use the same method to sample the negative electrode current collector and weigh the mass m2 of the negative electrode current collector sample. Calculate the sample area S obtained by the sampler. (m1-m2) / S is the surface density ρ of the negative electrode active material layer, which is expressed in g / m 2 .

[0064] 2. Test of B:

[0065] The batteries prepared in the examples and comparative examples were discharged at 0.33C, and the batteries were disassembled to measure the excess length of the battery separator relative to the negative electrode tab direction. The length is the dimension B in the present invention, in mm.

[0066] 3. Test of A:

[0067] The batteries prepared by the examples and comparative examples were discharged at 0.33C, and the negative electrode sheets were taken out and immersed in a dimethyl carbonate (DMC) solution for 2 hours. After being taken out, they were dried at 60°C for 12 hours.

[0068] Take a standard steel plate (50mmx125mm) as the rigidity test base plate, wipe the surface of the steel plate with dust-free paper dipped in alcohol, stick one side of the 50mmx125mm 3M double-sided tape on the steel plate, and ensure that the paste is flat and wrinkle-free; cut the negative electrode sheet with active coating into 50mmx125mm test samples; stick the electrode sheet to be tested on the other adhesive surface of the double-sided tape, and then stick another layer of double-sided tape on the surface of the electrode sheet. Ensure that the contact is flat and wrinkle-free during the pasting process. After rolling with a roller, use a universal testing machine to clamp the steel plate at one end and the 3M tape at the other end. Set the tensile machine stroke to 100mm, and do a pulling test at a speed of 300mm / min. Set the tensile machine stroke to 100mm, record the curve in the tensile machine software diagram. When the displacement is greater than 80mm, the machine stops, and read the average tensile force value of the flat part of the curve, which is the cohesive force A, in N / m.

[0069] 4. Test of C:

[0070] The alkaline dissolution-ICP method is used to test the silicon content in the negative electrode sheet. Specifically, the battery is discharged at 0.33C, cleaned with solvent DMC, soaked for 48 hours, and dried at 60℃ to scrape the powder of the negative electrode active material layer; weigh the powder sample, place it in a nickel crucible pre-filled with potassium hydroxide, add a little potassium hydroxide to cover the surface of the sample, drip two drops of ethanol, place it on an electric furnace and heat it until the potassium hydroxide melts and dehydrates, then move it to a muffle furnace at 1100℃, keep it molten and keep it warm for 8 hours, take out the nickel crucible, and cool it slightly. Put it in a 300mL plastic beaker, add hot water for extraction, and wash out the crucible after the reaction. Add HCl to the extract to acidify it, and add hydrogen peroxide and hydrochloric acid to form a mixed acid to make the silicon-containing compound more thoroughly converted to silicon ions; after cooling, wash it out with water, transfer it to a 100mL volumetric flask, dilute to volume, and shake it well. After standing, take the solution into another 100mL volumetric flask, dilute to volume, shake it well, stand and clarify, and obtain the solution to be tested. At the same time, prepare a blank solution as a control. No powder is added to the blank solution. Make a blank sample control according to the operating procedures to eliminate possible influences during the operation.

[0071] Perform ICP test on the solution to be tested, select the element detection spectrum wavelength, and set the experimental conditions: According to the characteristics of the sample and the solution to be tested, perform ICP test on the Si element detection spectrum wavelength of 288.158nm, and test the Si content of the element through ICP test.

[0072] The parameter conditions corresponding to the various embodiments and comparative examples obtained by the above test method are shown in Table 1.

[0073] Table 1

[0074]

[0075]

[0076] The performance test of the batteries of the embodiment and the comparative example under the above parameter conditions is carried out, and the test method is as follows:

[0077] Test 1-Safety performance test:

[0078] At 25°C, the fully charged lithium-ion battery was left standing, where the charging strategy was: charging the lithium-ion battery at 0.5C constant current to a cut-off voltage of 4.25V, and charging it at constant voltage to a cut-off current ≤0.05C; during the charging process, the open circuit voltage OCV was measured at regular intervals, and the voltage change and voltage drop (K value) were recorded. The K value calculation formula is (OCV1-OCV2) / (t1-t2), where a calculated K value <0.023 indicates normal, and other values ​​indicate a short circuit.

[0079] Test 2 - Energy Density Test:

[0080] a: Charge the battery at a constant current of 0.33C to an upper voltage of 4.25V, then charge at a constant voltage until the cut-off current is less than or equal to 0.05C, and then discharge;

[0081] Repeat the above steps 3 times, and take the third discharge energy as the discharge energy E of the battery;

[0082] b: The battery weight M is obtained by weighing with an electronic balance;

[0083] c: Calculation of weight energy density: E / M, unit: Wh / Kg.

[0084] Test 3-Cycle life @ 25℃ test:

[0085] The lithium-ion battery was placed at 25°C for 120 min, charged at 0.5C constant current to a cut-off voltage of 4.25V, charged at constant voltage to a cut-off current ≤ 0.05C, and after being placed at rest for 10 min, discharged at 0.5C constant current to 2.5V; the above was one cycle, and the above steps were repeated until 80% SOH was reached, and the number of cycles was recorded.

[0086] Based on this parameter condition, A 1 / 2 *The values ​​of C / B and the corresponding effects are shown in Table 2 below.

[0087] Table 2

[0088]

[0089] From the data results in Table 1 and Table 2, we can see that: 1 / 2 * When C / B is within the range of 0.03-3, a battery with high safety performance can be obtained while ensuring that the battery has good electrochemical properties such as good energy density and cycle performance. 1 / 2 * When the C / B value is in the range of 0.045-1.6, a battery with better comprehensive performance in terms of energy density and cycle performance can be obtained; or, when the silicon-based material contains silicon-carbon material, by further optimizing A 1 / 2 *When the C / B value is between 0.045 and 1, a battery with better comprehensive performance in terms of energy density and cycle performance can be obtained.

[0090] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A battery comprising a negative electrode sheet, a positive electrode sheet and a separator, wherein the negative electrode sheet comprises a current collector and a negative electrode active material layer arranged on the surface of the current collector, wherein the negative electrode active material layer comprises a silicon-based material, characterized in that: The cohesive force of the negative electrode sheet is A, in N / m; the separator is arranged parallel to the direction of the tab lead-out, close to the tab side, beyond the negative electrode sheet, and the dimension of the separator beyond the negative electrode sheet is B, in mm; the mass percentage of silicon in the negative electrode active material layer is C; A, B and C satisfy the following relationship: 0.03≤A 1 / 2 *C / B≤3.

2. The battery according to claim 1, characterized in that A 1 / 2 *The value of C / B is 0.045-1.

4.

3. The battery according to claim 1 or 2, characterized in that: The A is 0.3-220; And / or, B is 1-4; And / or, the C is 1.5%-30%.

4. The battery according to claim 3, characterized in that The A is 5-150; And / or, B is 1.5-3; And / or, the C is 4%-20%.

5. The battery according to claim 1 or 2, characterized in that: The surface density of the negative electrode active material layer is 60-300 g / m 2 .

6. The battery according to claim 1 or 2, characterized in that: The silicon-based material includes silicon-carbon material and / or silicon-oxygen material.

7. The battery according to claim 6, characterized in that When the silicon-based material comprises a silicon-carbon material, A 1 / 2 *The range of C / B is 0.045-1.

8. The battery according to claim 6, characterized in that The negative electrode active material layer also includes one or more of artificial graphite, natural graphite and hard carbon.

9. The battery according to claim 1, characterized in that The negative electrode active material layer includes a binder, and the binder includes PAA:SBR:CMC in a mass ratio of (34.38-74.29):(20-59.38):(5-7.14).

10. An electrical device, characterized in that: A battery comprising any one of claims 1 to 9.

Citation Information

Cited By

  • Negative plate and battery

    CN122370324A